Method for synthesizing diol from hemicellulose
By preparing a magnetic catalyst containing Ni, MgO and LaOx precursors, the problems of difficulty in the preparation of diols in hemicellulose are solved, and efficient and low-cost diol preparation is achieved.
Patent Information
- Application Number
- CN202411557971.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-03-11
AI Technical Summary
In the prior art, when using hemicellulose to prepare ethylene glycol, 1,2-propanediol and 1,2-butanediol, the catalyst is difficult to recover, the selectivity is low and prone to inactivation, resulting in lower production efficiency and yield.
A catalyst containing Ni, MgO and LaOx precursors is prepared by ultrasonic assisted dissolution, magnetic stirring, aging and calcining, and a magnetic catalyst with superparamagnetic and high recovery properties is obtained. The catalyst reacts with hemicellulose and deionized water at 180-290°C to form diol.
1,2-butanediol and other glycols were prepared from hemicellulose with high yield. The catalyst had good recycling and catalytic activity, low cost, and adjustable reaction conditions.
Smart Images

Figure FT_1 
Figure FT_2 
Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of diol preparation, and particularly relates to a method for synthesizing diol from hemicellulose. Background Art
[0002] Diols (ethylene glycol, 1,2-propylene glycol and 1,2-butylene glycol) are multifunctional and high-value platform chemicals. They are also important intermediates in the chemical industry with a wide range of uses and large market demand. Ethylene glycol is an important organic compound and chemical intermediate that can be widely used in many fields such as surfactants, antifreeze and plasticizers. It also plays a significant role in different fields such as energy, plastics, automobiles and chemicals, such as antifreeze and coolants in automobiles, deicing fluids for windshields and aircraft, desiccants for natural gas production, and precursors for the manufacture of polyester fibers and resins. 1,2-propylene glycol is not only widely used in building materials, chemical and pharmaceutical industries, as a monomer for the production of polyester resins, antifreeze, liquid detergents, biofuels, cosmetics and foods, but also in the manufacture of unsaturated polyester resins, antifreeze, biofuels and non-ionic detergents. 1,2-Butanediol has the characteristics of low viscosity and low freezing point, and is therefore widely used in the synthesis of polyester polyols, plasticizers, cosmetics, and pharmaceuticals (such as ethambutol, levetiracetam, and brivaracetam).
[0003] At present, the production route of ethylene glycol mainly uses ethylene as raw material and produces ethylene glycol through ethylene oxide. In addition, there is a coal chemical route that uses coal or natural gas as raw materials, first produces synthesis gas (CO + H2), and then produces ethylene glycol through direct or indirect methods. Propylene glycol is mainly produced in industry through the selective oxidation of non-renewable petroleum-derived propylene to propylene oxide and its subsequent hydration process. 1,2-Butanediol is mainly produced in industry through the acetylene aldehyde method, maleic anhydride method, butadiene method and propylene oxide method. The limited reserves of chemical resources have stimulated the development of a sustainable chemical industry, and the use of renewable biomass as raw materials to prepare diols is expected to overcome this shortcoming. In recent studies, there has been no relevant research on the direct production of 1,2-butanediol from hemicellulose. There are few studies on the simultaneous production of ethylene glycol and 1,2-propylene glycol from hemicellulose, which requires harsh conditions such as liquid acid hydrolysis and high temperature. The catalyst is easily lost during the recovery process, and some of the catalysts have low selectivity for ethylene glycol and 1,2-propylene glycol and are easily deactivated. As one of the three main components of biomass, hemicellulose is of great significance for the production of diols, especially 1,2-butanediol, with a high yield. Therefore, it is urgent to find an easily recyclable catalyst that overcomes the above shortcomings for the catalytic conversion of hemicellulose to produce ethylene glycol, 1,2-propylene glycol and 1,2-butanediol. Summary of the invention
[0004] The object of the present invention is to overcome the defects of the prior art and provide a method for synthesizing diols from hemicellulose.
[0005] The technical solution of the present invention is as follows: A method for synthesizing diols from hemicellulose, comprising: After adding hemicellulose, catalyst and deionized water into a reactor, the reactor is sealed, the air in the reactor is replaced with nitrogen, hydrogen is filled in and the pressure is increased to 1-10 MPa, and a closed reaction is carried out at 180-290°C for 1-10 hours, and then cooled to room temperature to obtain diol; The preparation method of the catalyst comprises the following steps: weighing a certain amount of metal precursor, dissolving it in an appropriate amount of deionized water under the assistance of ultrasound, slowly dripping a precipitant Na2CO3 solution under the condition of 800rpm magnetic stirring to adjust the pH value to 8.0, then continuously stirring and aging at 60-100℃ for 1-6h, then performing solid-liquid separation through a suction filtration device, and washing the precipitate with deionized water; drying the washed precipitate at 80-120℃ for 8-15h, cooling to room temperature, fully grinding it with a mortar and passing it through a 100-mesh sieve, and then calcining it in air at 300-500℃ for 3-7h to obtain a calcined product; reducing the calcined product in a tubular furnace at 300-600℃ and a 5% volume fraction H2-N2 atmosphere for 2-8h to obtain a catalyst; wherein the metal precursor is selected from LaO x The catalyst has superparamagnetism and can be recovered and recycled through magnetic separation.
[0006] In a preferred embodiment of the present invention, the mass ratio of hemicellulose, catalyst and deionized water is 0.1~1:0.05~0.5:20~40.
[0007] In a preferred embodiment of the present invention, the metal precursor is a Ni precursor and a MgO precursor, and the molar ratio of the Ni precursor to the MgO precursor is 0.1-2:1-10.
[0008] In a preferred embodiment of the present invention, the metal precursor is a precursor of Ni and LaO x The precursor of the Ni precursor and LaO x The molar ratio of the precursor is 1~5:1~10.
[0009] In a preferred embodiment of the present invention, the metal precursor is LaO x The LaO x The molar ratio of the precursor, the Ni precursor and the MgO precursor is: 1~10:0.5~5:5~20.
[0010] In a preferred embodiment of the present invention, the reduction temperature is 400-650°C.
[0011] In a preferred embodiment of the present invention, the Ni precursor is nickel nitrate or nickel nitrate hydrate, the MgO precursor is magnesium nitrate or magnesium nitrate hydrate, and the LaO x The precursor is lanthanum nitrate or lanthanum nitrate hydrate.
[0012] The beneficial effects of the present invention are: 1. The present invention can adjust Ni, MgO and LaO x The amount of precursor added is used to adjust the active sites and alkalinity strength of the catalyst and the reaction conditions, thereby preparing 1,2-butanediol with a higher yield.
[0013] 2. The magnetic non-precious metal catalyst prepared by the present invention has low cost, superparamagnetism, high magnetization intensity, and is extremely convenient and fast to recover.
[0014] 3. The magnetic catalyst prepared by the present invention has a simple preparation method and maintains excellent catalytic activity during recycling. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 : XRD patterns of representative catalysts.
[0016] Figure 2 : Magnetic hysteresis regression lines (a) and coercivity diagrams (b) of representative catalysts. DETAILED DESCRIPTION
[0017] In order to make the contents of the present invention easier to understand, the technical solution of the present invention is further described below in conjunction with specific implementation methods, but the present invention is not limited thereto.
[0018] The hemicellulose in the following examples: xylan was purchased from Aladdin Reagent (Shanghai) Co., Ltd., with the product number X140487.
[0019] The preparation method of the catalyst in the following embodiments comprises: Weigh a certain amount of metal precursor, dissolve it in an appropriate amount of deionized water under ultrasonic assistance, slowly add a precipitant Na2CO3 solution to adjust the pH value to 8.0 under 800rpm magnetic stirring, then continuously stir and age at 60~100℃ for 1~6h, then separate the solid and liquid through a suction filtration device, and wash the precipitate thoroughly with deionized water; dry the washed precipitate at 80~120℃ for 8~15h, cool to room temperature, grind it thoroughly with a mortar and pass it through a 100-mesh sieve, and then calcine it in air at 300~500℃ for 3~7h to obtain a calcined product; reduce the calcined product in a tubular furnace at 300~600℃ and a 5% H2-N2 atmosphere for 2~8h to obtain a catalyst. Wherein, the metal precursor is selected from Ni precursor, MgO precursor, LaO precursor, x precursor.
[0020] In Examples 1-13 of the present invention, the precursor of Ni is Ni(NO3)2·6H2O, the precursor of MgO is Mg(NO3)2·6H2O, and the precursor of LaO is x The precursor is LaN3O9·6H2O.
[0021] Examples 1-13 The catalyst preparation methods of Examples 1-13 are as follows: 0.012 mol Ni(NO3)2·6H2O, 0.036 mol Mg(NO3)2·6H2O and 0.012 mol LaN3O9·6H2O were dissolved in an appropriate amount of deionized water at room temperature and ultrasonicated for 20 min to obtain a mother liquor. Subsequently, a precipitant Na2CO3 solution was slowly added to the mother liquor under 800 rpm magnetic stirring to adjust the pH value to 8.0, and then the mixture was continuously stirred and aged at 80°C for 3 h, and then the solid-liquid separation was performed by a suction filtration device, and the precipitate was thoroughly washed with deionized water. The washed precipitate was dried at 120°C for 12 h, cooled to room temperature, fully ground with a mortar and passed through a 100 mesh sieve, and then calcined in air at 400°C for 4 h to obtain a calcined product. Finally, the calcined product was reduced in a tubular furnace at 500°C and a 5% volume fraction H2-N2 atmosphere for 5 h to prepare the catalyst Ni@MgO-LaO x (1:3:1). Similarly, by changing the molar ratio of Ni(NO3)2·6H2O, Mg(NO3)2·6H2O and LaN3O9·6H2O to 0.5:3:1, 2:3:1, 1:4:1, 1:2:1, 1:3:2 and 1:3:0.5, other catalysts with different metal molar ratios were prepared and named Ni@MgO-LaO x(x:y:z) catalyst, where x:y:z represents Ni, MgO and LaO x The molar ratio of Ni(NO3)2·6H2O, Mg(NO3)2·6H2O and LaN3O9·6H2O).
[0022] Preparation of Ni@MgO catalyst: 0.012 mol Ni(NO3)2·6H2O and 0.036 mol Mg(NO3)2·6H2O were dissolved in an appropriate amount of deionized water at room temperature and ultrasonicated for 20 min to obtain a mother liquor. The remaining preparation steps were similar to those of Ni@MgO-LaO x The preparation of the (1:3:1) catalyst is the same, the prepared binary metal catalyst is marked as Ni@MgO, and the metal molar ratio of active metal Ni and MgO is 1:3, which is marked as Ni@MgO (1:3).
[0023] Ni@LaO x Preparation of catalyst: Dissolve 0.012 mol Ni(NO3)2·6H2O and 0.012 mol LaN3O9·6H2O in an appropriate amount of deionized water at room temperature, and ultrasonicate for 20 min to obtain a mother solution. The remaining preparation steps are similar to those of Ni@MgO-LaO x The preparation of the (1:3:1) catalyst is the same, and the prepared binary metal catalyst is labeled as Ni@LaO x , active metals Ni, LaO x The metal molar ratio is 1:1, which is marked as Ni@LaO x (1:1).
[0024] MgO@LaO x Catalyst preparation: 0.036 mol Mg(NO3)2·6H2O and 0.012 mol LaN3O9·6H2O were dissolved in an appropriate amount of deionized water at room temperature and ultrasonicated for 20 min to obtain a mother solution. The remaining preparation steps were similar to those of Ni@MgO-LaO x The preparation of the (1:3:1) catalyst is the same, and the prepared binary metal catalyst is labeled as MgO@LaO x , active metals MgO, LaO x The metal molar ratio is 3:1, which is labeled as MgO@LaO x (3:1).
[0025] Single metal Ni, MgO and LaO xCatalyst preparation: A certain amount of Ni(NO3)2·6H2O, Mg(NO3)2·6H2O or LaN3O9·6H2O was dried at 120°C for 12 hours, cooled to room temperature, fully ground with a mortar and passed through a 100-mesh sieve, and then calcined in air at 400°C for 4 hours to obtain a calcined product. Finally, the calcined product was reduced in a tube furnace at 500°C and a 5% volume fraction H2-N2 atmosphere for 5 hours to prepare single metal Ni, MgO and LaO, respectively. x catalyst.
[0026] Catalytic reaction: 0.5 g of hemicellulose, 0.1 g of catalyst and 30 mL of deionized water were added to a stainless steel autoclave, and the autoclave was sealed. The air in the autoclave was replaced with nitrogen, and H2 was added to increase the pressure to 4 MPa. The reaction was carried out at 250 ° C for 5 h at a stirring rate of 800 rpm, and then cooled to room temperature to obtain diol.
[0027] It can be seen from Table 1 that Ni, MgO and LaO x When the single metal catalyst was used for the reaction, only Ni was reacted to obtain a trace amount of diol yield, indicating that the single metal catalyst was not effective in preparing 1,2-butanediol from hemicellulose; the results of using a bimetallic catalyst showed that Ni@MgO and Ni@LaOx were more effective in preparing diol from hemicellulose. When using a ternary metal catalyst with different metal molar ratios for the conversion, by comparing the different proportions of the three metals, it can be seen that in Ni@MgO-LaO x When the metal molar ratio of the catalyst was 1:3:1, the yield of 1,2-butanediol was the highest, reaching 21.4%, and the yield of total diols was 36.7%.
[0028] Table 1 Test results of Examples 1-13
[0029] XRD patterns of representative catalysts are shown in Figure 2. Figure 1 shown.
[0030] Figure 2 The hysteresis loop of the representative catalyst. The measurement results with the applied magnetic field at 10K show that all samples have a good hysteresis loop morphology, belonging to the S-type hysteresis loop, and the curve shows superparamagnetism. The saturation magnetization (Ms), remanent magnetization (Mr) and coercive force (Ce) of Ni@MgO (1:3) are Ms = 1.6 emu / g, Mr = 0.085 emu / g and Ce = 5 Oe, respectively, and that of Ni@LaO x(1:1) of Ms =13 emu / g, Mr = 1.94 emu / g and Ce = 167 Oe, Ni@MgO-LaO x (1:3:1) with Ms = 1.52 emu / g, Mr = 0.005 emu / g, and Ce = 2 Oe. These properties of the catalyst contribute to its unique catalytic ability while maintaining its superparamagnetic properties, allowing for simple separation and reuse by applying an external magnetic field without filtration or centrifugation.
[0031] The following Examples 14-43 use Ni@MgO-LaO x (1:3:1) catalyst was investigated under different reaction conditions and cycle experiments.
[0032] Examples 14-19 Add 0.5 g hemicellulose and 0.1 g Ni@MgO-LaO into a stainless steel autoclave. x The reactor was sealed after adding (1:3:1) catalyst and 30 mL of deionized water. The air in the reactor was replaced with nitrogen, and H2 was filled to increase the pressure to 4 MPa. The reaction was carried out in a closed state at 220-270 °C for 5 h at a stirring rate of 800 rpm, and then cooled to room temperature to obtain diol.
[0033] As shown in Table 2, under the reaction conditions of 220℃~270℃, the yield of 1,2-butanediol can reach more than 15%. As the temperature increases, the yields of ethylene glycol and 1,2-propylene glycol gradually increase. When the reaction temperature is 270℃, the total yield of diols can reach 48.0%.
[0034] Table 2 Test results of Examples 14-19
[0035] Examples 20-26 Add 0.5 g hemicellulose and 0.1 g Ni@MgO-LaO into a stainless steel autoclave. x The reactor was sealed after adding (1:3:1) catalyst and 30 mL of deionized water. The air in the reactor was replaced with nitrogen, and H2 was filled to increase the pressure to 4 MPa. The reaction was carried out in a closed state at 250 ° C with a stirring rate of 800 rpm for 2 to 8 hours, and then cooled to room temperature to obtain diol.
[0036] Table 3 Test results of Examples 20-26
[0037] It can be seen from Table 3 that the longer the reaction time, the more favorable it is for the formation of diols. The difference is that with the increase of time, the yield of the target product 1,2-butanediol first increases and then decreases, and the yields of ethylene glycol and 1,2-propylene glycol gradually increase overall. When the reaction time is 8h, the yield of total diols can reach 53.3%.
[0038] Examples 27-33 Add 0.5 g hemicellulose and 0.1 g Ni@MgO-LaO into a stainless steel autoclave. x The reactor was sealed after adding (1:3:1) catalyst and 30 mL of deionized water. The air in the reactor was replaced with nitrogen, and H2 was filled to increase the pressure to 2-8 MPa. The reaction was carried out in a closed state at 250 ° C with a stirring rate of 800 rpm for 5 hours, and then cooled to room temperature to obtain diol.
[0039] Table 4 Test results of Examples 27-33
[0040] As shown in Table 4, when the H2 pressure is low (2-3MPa), the yield of diols is low; when the H2 pressure is increased to 4MPa, the yield of 1,2-butanediol reaches 21.4% at the highest. As the H2 pressure continues to increase, the yield of 1,2-butanediol decreases, while the yields of ethylene glycol and 1,2-propylene glycol gradually increase; when the H2 pressure is 7MPa, the yield of total diols can reach 57.2%.
[0041] Examples 34-37 Add 0.5 g hemicellulose and 0.05-0.2 g Ni@MgO-LaO into a stainless steel autoclave. x The reaction kettle was sealed after adding (1:3:1) catalyst and 30mL deionized water. The air in the kettle was replaced with nitrogen, and H2 was filled to increase the pressure to 4MPa. The reaction was carried out in a closed state at 250℃ with a stirring rate of 800rpm for 5h, and then cooled to room temperature to obtain diol.
[0042] Table 5 Test results of Examples 34-37
[0043] As shown in Table 5, with the increase of catalyst dosage, the yield of diols gradually increases, and the increased diols are mainly 1,2-propylene glycol. When the amount of catalyst is 0.10g, the yield of 1,2-butanediol reaches 21.4%. When the amount of catalyst is 0.15g, the total yield of diols reaches 50.8%. After further increasing the amount of catalyst, the yield of diols does not change significantly; when the amount of catalyst is 0.20g, the yield of diols can reach 53.0%.
[0044] Examples 38-43 Using Ni@MgO-LaO x 0.5 g of hemicellulose and 0.1 g of Ni@MgO-LaO were added to the stainless steel autoclave. x (1:3:1) catalyst and 30mL deionized water were added and sealed. The air in the kettle was replaced with nitrogen, and H2 was filled to increase the pressure to 4MPa. The reaction was carried out in a closed state at 250°C for 5h at a stirring rate of 800rpm, and then cooled to room temperature to obtain diol. In the cycle experiment, the catalyst recovered by magnetic separation was vacuum dried at 80°C for 8h, fully ground and passed through a 100-mesh sieve, and directly used for the next experimental run without reduction again.
[0045] Table 6 Test results of Examples 38-43
[0046] It can be seen from Table 6 that Ni@MgO-LaO x (1:3:1) After the catalyst was reused for 5 times, the yield of total diols remained basically unchanged, the yield of 1,2-butanediol decreased slightly, while the yields of ethylene glycol and 1,2-propylene glycol increased slightly, indicating that the catalyst has excellent stability.
[0047] The above description is only a preferred embodiment of the present invention, and therefore cannot be used to limit the scope of the present invention. That is, equivalent changes and modifications made according to the patent scope of the present invention and the contents of the specification should still fall within the scope of the present invention.
Claims
1. A method for synthesizing diols from hemicellulose, characterized in that: After adding hemicellulose, catalyst and deionized water into a reactor, the reactor is sealed, the air in the reactor is replaced with nitrogen, hydrogen is filled in and the pressure is increased to 1-10 MPa, and a closed reaction is carried out at 180-290°C for 1-10 hours, and then cooled to room temperature to obtain diol; The preparation method of the catalyst comprises the following steps: A certain amount of metal precursor is weighed, dissolved in an appropriate amount of deionized water under the assistance of ultrasound, a precipitant Na2CO3 solution is slowly added dropwise under magnetic stirring to adjust the pH value to 8.0, and then the mixture is continuously stirred and aged at 60-100°C for 1-6 hours, and then solid-liquid separation is performed through a suction filtration device, and the precipitate is washed with deionized water; the washed precipitate is dried at 80-120°C for 8-15 hours, cooled to room temperature, fully ground with a mortar and passed through a 100-mesh sieve, and then calcined in air at 300-500°C for 3-7 hours to obtain a calcined product; the calcined product is reduced in a tubular furnace at 300-600°C and a 5% by volume H2-N2 atmosphere for 2-8 hours to obtain a catalyst; wherein the metal precursor is selected from a Ni precursor, a MgO precursor, a LaO precursor, a x precursor.
2. The method according to claim 1, characterized in that: The catalyst has superparamagnetism and can be recovered and recycled through magnetic separation.
3. The method according to claim 1, characterized in that: The mass ratio of hemicellulose, catalyst and deionized water is 0.1~1:0.05~0.5:20~40.
4. The method according to claim 1, characterized in that: The metal precursors are a Ni precursor and a MgO precursor, and the molar ratio of the Ni precursor to the MgO precursor is 0.1-2:1-10.
5. The method according to claim 1, characterized in that: The metal precursor is a Ni precursor and LaO x The precursor of the Ni precursor and LaO x The molar ratio of the precursor is 1~5:1~10.
6. The method according to claim 1, characterized in that: The metal precursor is LaO x The LaO x The molar ratio of the precursor, the Ni precursor and the MgO precursor is: 1~10:0.5~5:5~20.
7. The method according to claim 1, characterized in that: The reduction temperature is 400-650°C.
8. The method according to claim 1, characterized in that: The precursor of Ni is nickel nitrate or nickel nitrate hydrate, the precursor of MgO is magnesium nitrate or magnesium nitrate hydrate, and the precursor of LaO x The precursor is lanthanum nitrate or lanthanum nitrate hydrate.